Calcium, Magnesium, Potassium, and Sodium Oxybates Oral Solution: A Lower-Sodium Alternative for Cataplexy or Excessive Daytime Sleepiness Associated with Narcolepsy - Dauvilliers Y; Bogan RK; Šonka K; Partinen M; Foldvary-Schaefer N; Thorpy MJ (Nature and Science of Sleep, 2022)
Yves Dauvilliers,1,2 Richard K Bogan,3 Karel Šonka,4 Markku Partinen,5 Nancy Foldvary-Schaefer,6 Michael J Thorpy7 1Sleep and Wake Disorders Centre, Department of Neurology, Gui de Chauliac Hospital, Montpellier, France; 2University of Montpellier, INSERM Institute Neuroscience Montpellier (INM), Montpellier, France; 3University of South Carolina School of Medicine, Columbia, SC, USA; 4Department of Neurology, First Faculty of Medicine, Charles University and General University Hospital, Prague, Czech Republic; 5Helsinki Sleep Clinic, Terveystalo Healthcare, and Department of Clinical Neurosciences, University of Helsinki, Helsinki, Finland; 6Sleep Disorders Center, Department of Neurology, Cleveland Clinic, Cleveland, OH, USA; 7Department of Neurology, Albert Einstein College of Medicine, Bronx, NY, USACorrespondence: Yves Dauvilliers, 80 Avenue Augustin Fliche, Montpellier, 34295, France, Tel +334 67 33 72 77, Email ydauvilliers@yahoo.frAbstract: Lower-sodium oxybate (LXB) is an oxybate medication approved to treat cataplexy or excessive daytime sleepiness (EDS) in patients with narcolepsy 7 years of age and older in the United States. LXB was developed as an alternative to sodium oxybate (SXB), because the incidence of cardiovascular comorbidities is higher in patients with narcolepsy and there is an elevated cardiovascular risk associated with high sodium consumption. LXB has a unique formulation of calcium, magnesium, potassium, and sodium ions, containing 92% less sodium than SXB. Whereas the active oxybate moiety is the same for LXB and SXB, their pharmacokinetic profiles are not bioequivalent; therefore, a phase 3 trial in participants with narcolepsy was conducted for LXB. This review summarizes the background on oxybate as a therapeutic agent and its potential mechanism of action on the gamma-aminobutyric acid type B (GABAB) receptor at noradrenergic and dopaminergic neurons, as well as at thalamocortical neurons. The rationale leading to the development of LXB as a lower-sodium alternative to SXB and the key efficacy and safety data supporting its approval for both adult and pediatric patients with narcolepsy are also discussed. LXB was approved in August 2021 in the United States for the treatment of idiopathic hypersomnia in adults. Potential future developments in the field of oxybate medications may include novel formulations and expanded indications for other diseases.Graphical Abstract: Keywords: narcolepsy, therapeutics, drug development, cataplexy, excessive daytime sleepiness, idiopathic hypersomnia